1989
DOI: 10.1093/bja/62.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ambu Cpap System

Abstract: We have assessed a Venturi driven device for delivering continuous positive airway pressure (CPAP) using a reservoir bag and expiratory valve under conditions of continuous flow and simulated spontaneous breathing. The system performed well and was economical, consuming only 3.5 litre min-1 of fresh gas. One Venturi was partially blocked and performed inadequately, but the function of a second one was close to the manufacturer's specification (inspired oxygen 33%, flow 20 litre min-1 against end-expiratory pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This agrees with published data, and it was also found that they are somewhat position sensitive. 7 The Vital Signs valves showed less pressure alteration with flow, but some individual valves deviated noticeably from their nominal resistance value.…”
Section: The Prince Of Wales Hospital (Pow) Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…This agrees with published data, and it was also found that they are somewhat position sensitive. 7 The Vital Signs valves showed less pressure alteration with flow, but some individual valves deviated noticeably from their nominal resistance value.…”
Section: The Prince Of Wales Hospital (Pow) Systemmentioning
confidence: 93%
“…The Downs'-Vital Signs system The Downs' adjustable flow generator is an oxygen-driven jet venturi, with an adjustable oxygen bypass which serves to increase the oxygen concentration in the delivered gas. 7 It is designed to deliver total gas flows in the 25 to 100 l.min -1 range and can be connected through a suitable corrugated tube to a Vital Signs CPAP mask. The latter is a clear plastic mask with a large inflatable cushion to prevent pressure effects to the patient's face.…”
Section: The Auspap Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…These fluctuations in Paw have to be prevented, to keep the CPAP level constant during the entire respiratory cycle, thus reducing the imposed work of breathing (WOB) [4], incidence of barotraumas [l, 51 and changes in heart rate variability [6]. Since the end of the 1970s, many researches emerged about expiratory valves [ 1,3], development of low-WOB CPAP systems [2,7,81 and evaluation of these and the commonly used CPAP systems in various situations [4, [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%